The implementation of the convention on the rights of the child to legal system of the Republic of Kazakhstan (International relations and international law Journal, 2019)
Abstract. Special significancein the study of the problems of the implementation of internationallaw into national legislation is acquiredin the context of the implementation of international standardsin the field of juvenile rights. In the modern period, the problem of implementing the norms of theof theUnited Nations Convention on the Rights of the Child, adopted by General Assembly resolution 44/25,opened for signature in the city of New York on November 20, 1989, and other international treatiesinto the national legislation of the Republic of Kazakhstan is being actualized. This article monitors andanalyzes the practical realization of the International Acts on protection the interests and rights of thechild, ratified in the Republic of Kazakhstan, and other documents concern the Juvenile Justice System.The research accomplished in the context of the entire array of the current Law System of the Republicof Kazakhstan, focused on the implementation the international standards for the protection of HumanRights in general and particular in the Rights of the Child. Basing on the Civil Law legislation of the Republicof Kazakhstan,criteria are considered for the legal capacity of minors. The civil procedural capacityof minors is analyzed on the basis of the Civil Procedure Code. The principle of the best safeguardingof children’s rights, the need for its primary consideration in activities related to children, is enshrined incodified and other laws of the Republic of Kazakhstan, in which state policy in the interests of children isrecognized as a priority area of activity of state authorities. In accordance with the aim of the study, theproblem of the implementation in the national legislation of the norms of the United Nations Conventionon the Rights of the Child is analyzed.Key words: minor, rights, convention, implementation, Convention on the Rights of the Child.